The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/0953531032000111781
|View full text |Cite
|
Sign up to set email alerts
|

Growth of US Industries and Investments in Information Technology and Higher Education

Abstract: This paper presents new data on the sources of growth for the US economy over the period 1977-2000. Our principal innovation is the incorporation of detailed information for individual industries, including those involved in the production of information technology equipment and software. We show that economic growth is dominated by investments in information technology and higher education, both for individual industries and the economy as a whole. We also show that a jump in information technology investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 32 publications
3
68
0
3
Order By: Relevance
“…In the US, the total stock of quality-adjusted computer equipment in constant prices increased with a growth rate of 20% over several years with its peak of about 30% p.a. in the 1990s (Jorgensen/Stiroh, 2000;Jorgensen/Ho/Stiroh (2002)). …”
Section: Introductionmentioning
confidence: 99%
“…In the US, the total stock of quality-adjusted computer equipment in constant prices increased with a growth rate of 20% over several years with its peak of about 30% p.a. in the 1990s (Jorgensen/Stiroh, 2000;Jorgensen/Ho/Stiroh (2002)). …”
Section: Introductionmentioning
confidence: 99%
“…5 As mentioned above, the more recent macro literature has focused on the impact of ICT on the productivity growth in the U.S. After a period of productivity slowdown since the 1970s, the rapid productivity growth of the late 1990s in the U.S. -often referred to as "the U.S. productivity revival" -attracted much attention from the researchers. Most studies (for example, [14,41,44,45,46,71,78]) concluded that the unprecedented advances in ICT explained a significant part of the resurgence of U.S. productivity growth. 6 Wolff [83] further showed that, while computerization has a significant positive effect on total factor 4 Apte and Nath [7] give a brief account of the shift of the U.S. economy toward information services in the early 1990s.…”
Section: Information Servicesmentioning
confidence: 99%
“…The Domar-weighted aggregation was later adopted into the APPF framework in Jorgenson et al (1987) to exercise direct aggregation across industries to account for the role of American industries in the changes in aggregate inputs. It has since been used in Jorgenson et al (2005aJorgenson et al ( , 2005b to quantify the role of information technology (IT)-producing and IT-using industries in the US economy. The approach is now the international standard and has also been applied to the Chinese economy in Cao et al (2009) In this equation, Y is output, K is an index of capital service flows, L is an index of labour service flows and M is an index of intermediate inputs purchased from domestic industries and/or imported.…”
Section: Accounting For Industry Origin Of Tfpmentioning
confidence: 99%